The impact of internet use on adolescents’ health: empirical evidence from China - Du, Nianyu; Liu, Lele; Zhang, Lianpan; Yin, Shijiu (Frontiers in Psychiatry, 2024)
Background: With the continuous improvement in economic levels in various countries and the rapid development of the Internet, adolescents’ Internet use has become increasingly frequent. Many studies have explored the relationship between Internet use and adolescent health, but the possible mechanisms involved are unclear, and few have focused on Chinese adolescents. Methods: Based on the data from the China Family Panel Studies 2010, 2014, 2016, 2018, and 2020, this study used the ordered probit model and OLS model to explore the impact of Internet use on self-rated health and mental health of Chinese adolescents and analyzed the possible mechanisms and heterogeneity involved. Results: The results revealed that adolescents’ Internet use negatively affected their physical and mental health. Parent-child conflict, academic performance, and self- efficacy were the important mechanisms of internet use affecting adolescents’ health. Moreover, the negative effects of Internet use on adolescents' physical and mental health were heterogeneous in boarding, mother's education level, and family per capita income. Conclusion: Adolescents exhibit a pattern of using the internet that influences their health status. Our finding that internet use may decrease adolescents' health provides important insights into understanding the relationship between internet use behavior and adolescents' health and suggests that intervention should be taken on adolescents' internet use.